The Effect of Patient Characteristics and Sleep Quality on Visual Field Performance Reliability - Swarup S. Swaminathan; Matthew B. Greenberg; Elizabeth A. Vanner; Kara M. Cavuoto; Sarah R. Wellik; Ta Chen Chang (Journal of Ophthalmology)
Purpose. To investigate the association of automated visual field (VF) reliability indices (false positive [FP], false negative [FN], and fixation loss [FL]) and sleep quality, VF experience, and age. Methods. Prospective, cross-sectional study. Adult patients (age ≥ 18 years) completing automated VF testing were invited to participate. Baseline participant characteristics were obtained, and all participants were asked to complete the Pittsburgh Sleep Quality Index (PSQI) questionnaire. Nonparametric Spearman correlations and logistical regression models were performed. Results. 63 patients were enrolled. Lower PSQI score was correlated with higher percentage (%) FL in the right eye (p=0.03). Fewer prior VF was significantly correlated with higher %FP in the right eye (p=0.008). Older age was significantly correlated with higher %FN in the left eye (p=0.01). Greater mean deviation (MD) and pattern standard deviation (PSD) were strongly correlated with higher %FN in the right (p=0.02 and 0.002, resp.) and left eyes (p=0.01 and 0.02, resp.). Conclusion. In this prospective, cross-sectional study, worse MD and PSD are strongly correlated with increased FN in both eyes. Increased FN in the left eye associated with older age might be attributable to test fatigue. Worse sleep quality is associated with decreased FL in the right eye.